EFEKTIFITAS Beauveria bassiana VUILL TERHADAP PENGENDALIAN Spodoptera exigua HUBNER (LEPIDOPTERA : NOCTUIDAE) PADA TANAMAN BAWANG MERAH LOKAL PALU (Allium wakegi) - razak, Nurhidayah abd.; Nasir, Burhanuddin; Khasanah, Nur (AGROTEKBIS, 2016)
The purpose of this study is to determine the effectiveness of Beauveria bassiana on the control of Spodoptera exigua Hubner ( Lepidoptera : Noctuidae ) on shallot crop varieties Palu valley ( Allium wakegi ) . This research was conducted in the village of Sidera , District Biromaru , Sigi and in the Laboratory of Plant Pests and Diseases ( HPT ) .The research was conducted from April to June 2014. This study was prepared by Group Random Design ( RAK ) with patterns of factorial , consisting of 2 factors with 3 replications , in order to obtain 24 units experiment , with treatments as follows : F1 namely doses : D0 : Without the application of Beauveria bassiana / use distilled water , D1 : 6 grams B.bassiana / L of water , D2 : 8 gr B.bassiana / L of water , D3 : 10 gr B.bassiana / L of water and F2 is the time interval applications with 2 levels : W1 : interval of 5 days and W2 : interval of 7 days . The data were analyzed using analysis of variance ( ANOVA ) and if it shows a marked influence further tested using the Test HSD 5 % . Based on observations indicate that the fungus application B.bassiana significantly affect the intensity of the attacks S.exigua , during the observation time 4,5,6,7 and 8 MST show that the intensity of the treatment D3W1 provide S.exigua the lowest compared to all other treatments at an all-time observation . In observation of 4 MST intensity of the attack only reached 2.02% , on the observation 5MST reached 1.74% , at 6MST 7MST 1.39 % and 1.19 % . In observation of severe crop production ( Table 2 ) showed that the treatment D3W1 (10g / L , 5H ) produced the highest plant weight 143,82g / clump converted can reach 3.60 t / ha-1.Â Key Words : Beauveria bassiana , a local Shallot Crop Palu , Spodoptera exigua